Outcome Analysis and Determinants of Major Adverse Cardiac Events in Young Adults After Coronary Artery Bypass Graft Surgery Who Participated in Early Phase II Cardiac Rehabilitation Program: A single-centre study - Radi, Basuni Radi; Intan, Ryan Enast; Dwiputra, Bambang; Desandri, Dwita R; Ambari, Ade Meidian (Jurnal Kardiologi Indonesia, 2024)
Background: Cardiac rehabilitation (CR) program is proven to reduce mortality risk after coronary artery bypass surgery (CABG). Our study aimed to investigate the determinants of survival in young adult patients after CABG. Method: This was a single-centre, longitudinal study with a survival analysis method from MACE of consecutive patients under 55 years old who underwent CABG and participated in the early phase II CR program between January 2017 and December 2018. The major adverse cardiac events (MACE) rates were determined over a 2-year follow-up time. Cox regression and Kaplan-Meier analysis were used to determine the predictors of the events based on the data registry. Result: 279 patients who fulfilled the inclusion criteria were recruited in this study. MACE happened to 23 (8.45%) of them (3 patients died, 20 patients were hospitalised). Patients who dropped out (12%) from the CR program had a higher risk of developing events (HR 3.86, 95% CI 1.36-10.99). Of those who completed the CR program (245 patients), beta-blocker usage, chronotropic index, resting heart rate, and functional capacity after the CR program independently correlated with MACE. Six-minute walk distance (6-MWD) 376 meters was a significant predictor (p=0.001), with a shorter mean survival time of 6 months. Conclusion: The early phase II CR program after CABG in young adult patients reduced the risk for cardiovascular mortality, major adverse events, and related readmission. It also increased the survival rate and mean survival time for participants who completed the CR program compared to dropouts. Optimum beta blocker medication, chronotropic index, resting heart rate, and functional capacity after the CR program are essential predictors of survival after CABG in young adults.